2020
DOI: 10.1088/1361-6528/aba3db
|View full text |Cite
|
Sign up to set email alerts
|

CNT-coated magnetic self-assembled elastomer micropillar arrays for sensing broad-range pressures

Abstract: Cost-effective and broad-range flexible pressure sensors are highly desirable for use in wearable electronic devices for a wide range of sensitive measurements, from pulse to dynamic human motion. Herein, we present a high-performance flexible pressure sensor based on carbon nanotube-coated elastomer micropillar arrays (EMPAs). The EMPAs are prepared using a facile magnetic-field-induced self-assembly technique, which provides a simple and low-cost strategy to fabricate microstructured elastomers for construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…In a dual-mode sensing system, the tactile mode involves the perception of physical contact or interaction with objects, as shown in Figure b, while the touchless mode refers to the sensing of objects or environments without direct physical contact. The system’s ability to perceive and decouple these modes is crucial for its functionality and performance, and this ability is greatly influenced by its morphology and structure. The surface pattern of the B-MIGS consisted of neatly arranged triangular arrays, forming a parallel grid structure with a wider top and a narrower bottom, as shown in Figure c­(I),(II) and Figure S2b. The enlarged cross-sectional view of two adjacent grid gaps is shown in Figure c­(III), where nickel particles presented a distinct chainlike arrangement along the direction of the magnetic field, forming a robust backbone structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a dual-mode sensing system, the tactile mode involves the perception of physical contact or interaction with objects, as shown in Figure b, while the touchless mode refers to the sensing of objects or environments without direct physical contact. The system’s ability to perceive and decouple these modes is crucial for its functionality and performance, and this ability is greatly influenced by its morphology and structure. The surface pattern of the B-MIGS consisted of neatly arranged triangular arrays, forming a parallel grid structure with a wider top and a narrower bottom, as shown in Figure c­(I),(II) and Figure S2b. The enlarged cross-sectional view of two adjacent grid gaps is shown in Figure c­(III), where nickel particles presented a distinct chainlike arrangement along the direction of the magnetic field, forming a robust backbone structure.…”
Section: Resultsmentioning
confidence: 99%
“…First, silicone rubber (RTV-2) and silicone oil (viscosity: 0.05 Pa s; provided by Corning, Inc., USA) were fully mixed in a weight ratio of 3.2:1. Second, nickel particles (diameter: 0.8 μm; provided by China Metallurgical Xindun Alloy, China) were added to the silicone rubber mixture at different mass fractions (40,50,60, and 70 wt %). After 15 min of ultrasonication and 1 h of mechanical stirring, the mixture was mixed with a curing agent by stirring vigorously for 10 min and poured into a grid-shaped mold with a fixed depth of 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have previously reported that tactile sensors with unique microstructures, such as micropillars 59 , microdomes 160 , and microwrinkles 161 , 162 , can achieve better sensing performance than those with planar geometry. However, the fabrication of such microstructures usually involves expensive and complex processes.…”
Section: Applications Of Magneto-responsive Artificial Ciliamentioning
confidence: 99%
“…11f ) 58 . One such example is the work of Jing et al, who proposed a novel method for creating pressure sensors using self-assembled magnetic cilia coated with carbon nanotubes (CNTs) 162 . Specifically, the researchers first prepared a magnetic cilia array via the self-assembly process of a mixed solution of CI particles and PDMS.…”
Section: Applications Of Magneto-responsive Artificial Ciliamentioning
confidence: 99%
“…14,15 In contrast, the bottom-up approach constructs patterned nanostructures through the self-assembly of molecules or particles. 16,17 Self-assembly is a technique in which basic structural units (molecules, nanomaterials, substances at the micron or larger scale) spontaneously form ordered structures. 18,19 This process usually uses a liquid medium to allow the particles to move freely for self-assembly and functions in the nanoscale size range.…”
Section: Introductionmentioning
confidence: 99%